The Importance of Sex Education Literacy in Efforts to Prevent Sexual Violance in Children - Nur Prakoso, Muhammad Rizky (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Technological developments cause people to be able to access what they want, especially about sex and anything related to it.Wrong education can influence and give rise to the consequences of sexual abuse by children in their future development phase.The phenomenon of violence and sexual harassment that is detrimental to children in their own environment is caused by severalfactors, one of which is the lack of sex education for children. This study aims to provide encouragement to educators, especiallycounselors to provide preventive services related to sex education literacy to children through classical services as early as possiblein an effort to protect themselves. The research method used was observation, literacy studies, and case studies of 10 child victimsof sexual abuse in Sleman. The results of the study show that children are very easily influenced by the invitation of sexualharassment perpetrators, so it is necessary to have sex education literacy and self-protection by parents, schools, and relatedsocial services so that children always understand that sexual harassment can be committed by anyone, including those closestto them. they. Provisions from sex education literacy are expected to prevent sexual harassment, so that children can grow anddevelop in healthy physical and spiritual conditions.Keywords: Sex Education Literacy, Sexual Harassment, Parents, children's mental development.